Microcrédito como ferramenta de geração de renda e emprego: uma análise de experiências públicas municipais - Conceição, Jorge Henrique Muniz da (2005)
The goal of this work is to study microcredit public policy as a mechanism of improving wage and decreasing unemployment rates. This study is contextualized by analysis of up-to-date macroeconomic national situation, Brazilian intergovernamental constitutional relationship, Brazilian job market and local development perspectives, trying to show that public microcredit driven by local government is a natural and useful way. Two cases have been chosen for analysis: Banco do Povo de Juiz de For a and São Paulo Confia.